Stereoselective synthesis of the C79–C97 fragment of symbiodinolide - Takamura, Hiroyoshi; Fujiwara, Takayuki; Kadota, Isao; Uemura, Daisuke (Beilstein Journal of Organic Chemistry, 2013)
Symbiodinolide is a polyol marine natural product with a molecular weight of 2860. Herein, a streamlined synthesis of the C79–C97 fragment of symbiodinolide is described. In the synthetic route, a spiroacetalization, a Julia–Kocienski olefination, and a Sharpless asymmetric dihydroxylation were utilized as the key transformations.
Keywords: Julia–Kocienski olefination; polyol marine natural product; Sharpless asymmetric dihydroxylation; spiroacetalization; symbiodinolide